Evidence‐based practice within supervision during psychology practitioner training: A systematic review. (18th August 2019) - Barrett, Jessica; Gonsalvez, Craig J.; Shires, Alice
Abstract: Background: Supervision has long been recognised as a highly influential aspect of training within psychology. The scientist–practitioner model underpins postgraduate psychology training programs. During such programs, clinical supervision plays an important role in the development and acquisition of evidence‐based practice and scientist–practitioner competence. Objective: The primary objective of this study was to provide a comprehensive, current, and systematic review of the empirical research on supervisory interventions or practice that monitored and/or shaped the development of scientist–practitioner competence among psychology trainees. The secondary objective was to conduct a critical appraisal and assess the methodological rigour of included studies. Methods: Four major electronic databases were systematically searched against a priori inclusion criteria. Eligible quantitative studies investigated were located and assessed to identify evidence‐based practice and scientist–practitioner factors within supervision in the psychology training settings. Results: A large pool of studies was retrieved but only four studies ( N = 724 participants) met inclusion criteria indicating a major gap in the area. A narrative synthesis was conducted. Included studies were of good methodological quality, had small to medium sample sizes, and produced significant and valid results. Included studies used competency evaluation rating forms and compared supervision interventions. Conclusions: Despite the large body of literature on supervision, this review highlights a lack of empirical investigations into evidence‐based practice and scientist–practitioner competence within supervision during psychology training. Future research directions are provided, and recommendations and implications for training and supervision are discussed.